The prevalence of pelvic floor disorders and degree of bother among women attending primary care clinics in Armenia. (March 2020) - Badalian, Samuel S.; Sagayan, Elena; Simonyan, Hambardzum; Minassian, Vatche A.; Isahakian, Anna
Highlights: Pelvic floor disorders in Armenia are common and significantly correlated with demographic characteristics and co-morbidities The patients who underwent prior anti- incontinence or pelvic organ prolapse surgeries in Armenia, had higher PFBQ scores, suggesting that the surgeries may not have been performed properly resulting in more problems It is imperative to start promoting proper training of physicians in Female Pelvic Medicine and Reconstructive Surgery in Armenia Abstract: Objective: To explore the prevalence of various Pelvic Floor Disorders (PFD) and the degree of symptom bother in a convenience sample of Armenian women in the Republic of Armenia. Methods: Fifty women ages 20-85 years from each Armenian region (Marz) were included in the study. The survey included the validated Armenian version of the Global Pelvic Floor Bother Questionnaire (PFBQ) and general questions on demographics and comorbidities related to these disorders. Results: A total of 540 women (90%) attending primary care clinics completed the validated PFBQ questionnaire. Initial analysis showed that the PFBQ score was significantly higher in older women, and those with higher vaginal parity and BMI. Women with prior hysterectomy (37.1+ 22.4) and prior pelvic prolapse or anti-incontinence surgeries (40.6+ 21.6) had significantly higher PFBQ scores than women without prior surgeries (18.8+ 20, 0 and 19.4+ 19.7) and were associated with an increased odds of developing pelvic prolapse symptoms and obstructed defecation. Conclusions: PFD symptoms were observed to be common and significantly correlated with demographic characteristics and self-reported comorbidities in Armenian women. We need to start promoting proper training of physicians in Female Pelvic Medicine and Reconstructive Surgery.